Phosphate transporters in marine phytoplankton and their viruses: cross-domain commonalities in viral-host gene exchanges - Monier, Adam (Blackwell Publishing Ltd, 2012)
Phosphate (PO(4)) is an important limiting nutrient in marine environments. Marine cyanobacteria scavenge PO(4) using the high-affinity periplasmic phosphate binding protein PstS. The pstS gene has recently been identified in genomes of cyanobacterial viruses as well. Here, we analyse genes encoding transporters in genomes from viruses that infect eukaryotic phytoplankton. We identified inorganic PO(4) transporter-encoding genes from the PHO4 superfamily in several virus genomes, along with other transporter-encoding genes. Homologues of the viral pho4 genes were also identified in genome sequences from the genera that these viruses infect. Genome sequences were available from host genera of all the phytoplankton viruses analysed except the host genus Bathycoccus. Pho4 was recovered from Bathycoccus by sequencing a targeted metagenome from an uncultured Atlantic Ocean population. Phylogenetic reconstruction showed that pho4 genes from pelagophytes, haptophytes and infecting viruses were more closely related to homologues in prasinophytes than to those in what, at the species level, are considered to be closer relatives (e.g. diatoms). We also identified PHO4 superfamily members in ocean metagenomes, including new metagenomes from the Pacific Ocean. The environmental sequences grouped with pelagophytes, haptophytes, prasinophytes and viruses as well as bacteria. The analyses suggest that multiple independent pho4 gene transfer events have occurred between marine viruses and both eukaryotic and bacterial hosts. Additionally, pho4 genes were identified in available genomes from viruses that infect marine eukaryotes but not those that infect terrestrial hosts. Commonalities in marine host-virus gene exchanges indicate that manipulation of host-PO(4) uptake is an important adaptation for viral proliferation in marine systems. Our findings suggest that PO(4)-availability may not serve as a simple bottom-up control of marine phytoplankton.